Model of Zakat Utilization Based on Local Geographical Potential in West Sumatra - Fahlefi, Rizal (UIN Sunan Kudus, 2022)
Utilizing Zakat through a variety of productive programs can improve the welfare of the Muslim community and foster a sense of mental independence among them. Through the Boerka Superior Goat Breeding Center Program in Tanah Datar Regency, West Sumatra, this study aims to investigate how zakat is utilized based on the local geographical potential. Case study methodology is used as the qualitative research approach. Interviews and observations are employed as data collection techniques. The data analysis was conducted using the interactive data analysis model. According to the findings, the model consists of three phases: planning, implementation, and monitoring and evaluation. Several activities comprise the preparation of the program, including the formation of a management team, the selection of areas and mustahiks, and the provision of goats, forage seeds, and mentors. As part of the program's implementation, selected mustahiks will receive assistance in the form of training in recording, pen construction, disease prevention, and feed processing. During the monitoring and evaluation phase, the team conducted routine and ongoing monitoring and assessed the program's progress. This new basis in the utilization of zakat must be considered and implemented by zakat institutions, as it is insufficient to consider only the human factor, as local potential factors, including geographical potential, are also important in the utilization of zakat. Using zakat in a manner that prioritizes local geographical potential is anticipated to significantly enhance the quality of life for mustahiks.